Generalized absence seizures: Where do we stand today? - Stefan, Hermann; Trinka, Eugen (Zeitschrift für Epileptologie, 2022)
Generalized absence seizures are discussed here with respect to changing scientific concepts and newer findings, challenging the strict dichotomy of "generalized" vs. "focal" which may be counterproductive to the development of new ideas and treatments. Data from semiology, structural, and functional studies using quantitative electroencephalography (EEG), video-EEG monitoring, magnetoencephalography, magnetic resonance imaging, and positron emission tomography as well as neuropathology suggest a nosological spectrum from focal to generalized seizure-generating mechanisms. The terms "focal" and "generalized" as used to describe seizures represent abstractions and idealizations rather than ontological entities. The new terminology and classification of the ILAE (2017), despite its enormous merits, unfortunately also facilitates and fosters reductionist thinking, which may be pragmatic from a utilitarian perspective, but risks hindering scientific developments for the future. For instance, the seizure semiology of absences as a paradigmatic generalized seizure type is now classified as "non-motor seizure." A detailed phenomenological analysis reveals that motor activity is an integral part of this seizure type. Many motor and so-called automatic absence symptoms can be understood as correlated elements of a general organization plan of the cortex. Corresponding functional and structural changes seen in imaging and high-resolution electrophysiology studies indicate focal contributions to seizure generation and a combination of focal and generalized features. Functional findings indicate that the frontal lobe with its projections to other brain areas may play an important role in generalized absence seizures. In this critical review we assess the evolution of pathophysiological concepts through the ages and present new research approaches for diagnosis and treatment.
CRIS-Team WoS Importer:2022-02-18